Understanding and controlling inversion boundaries in ZnO. (1st May 2022) - Scheiber, Daniel; Popov, Maxim N.; Supancic, Peter; Spitaler, Jürgen
Abstract: In this paper, we report a study of the head-to-head (-O-Zn-O-) inversion boundaries (IB) in zinc oxide. We investigate the effect of impurities (Fe, Bi, Pr, Sn, Ti, and Sb) on the IB formation using ab-initio calculations in the framework of density-functional theory (DFT) for different atomic coverages. In agreement with experiment, DFT predicts spontaneous formation of IBs in Sb-, Sn-, and Fe-doped ZnO, with coverages of 1/3, 1/2, and 1 monolayer, respectively. Half a monolayer of Ti also lowers the IB formation energy, but brings it to about 1 J/m 2, which is not enough to trigger IB formation. Bi and Pr do not sufficiently promote IB formation at conditions relevant for ZnO sintering. Inspired by the remarkable success of DFT for evaluation of IB energies, we discuss the implications for the IB design and control.